Adaptation of targeted nanocarriers to changing requirements in antimalarial drug delivery - Marques, Joana (2017)
The adaptation of existing antimalarial nanocarriers to new Plasmodium stages, drugs, targeting molecules, or encapsulating structures is a strategy that can provide new nanotechnology-based, cost-efficient therapies against malaria. We have explored the modification of different liposome prototypes that had been developed in our group for the targeted delivery of antimalarial drugs to Plasmodium-infected red blood cells (pRBCs). These new models include: (i) immunoliposome-mediated release of new lipid-based antimalarials; (ii) liposomes targeted to pRBCs with covalently linked heparin to reduce anticoagulation risks; (iii) adaptation of heparin to pRBC targeting of chitosan nanoparticles; (iv) use of heparin for the targeting of Plasmodium stages in the mosquito vector; and (v) use of the non-anticoagulant glycosaminoglycan chondroitin 4-sulfate as a heparin surrogate for pRBC targeting. The results presented indicate that the tuning of existing nanovessels to new malaria-related targets is a valid low-cost alternative to the de novo development of targeted nanosystems.